Peran Dan Fungsi Bahasa Sebagai Komponen Utama Dalam Komunikasi Bisnis - Sarah Robiatul Adawiyah; Dudang Abdul Karim; Susi Fitria (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2024)
Language is used as a communication tool because with language someone can express ideas, ideas and thoughts. Not only in everyday life but in the business world, language is the main thing to pay attention to in order to create a good and successful business. In business activities, communication is an important factor in establishing relationships between business people and consumers. In business activities, the use of language has a very important role and function. Good language will have a positive effect so that business processes run smoothly and as expected. Business is a production, sales, marketing activity carried out by individuals, organizations or groups to gain profit. To run a business well, a person needs a good attitude, creativity, agility and good language skills. Language is a part of business communication ethics that needs to be considered. The method in this research uses a qualitative method with a descriptive approach, the aim is to describe the role and function of language as the main component of communication in business activities. From the results of this research it was found that the importance of using language in business communication includes several things such as the role and function of language as a component of the main tool of business communication, a means to facilitate promotion, a means to facilitate branding, a means to facilitate marketing, and a means to expand networks to the global level.